The McDonaldization of society - Ritzer, George (Los Angeles : Sage, 2015)
The McDonaldization of Society is George Ritzer's seminal work of critical sociology that links classical sociological theory to many aspects of contemporary life in a globalized world--Max Weber's rationalization thesis updated and applied to the late 20th and early 21st century. Where Weber focused on bureaucracies as the'iron cages' of rationalization in his time, the central premise of McDonaldization is that the fast food restaurant has become the model for the rationalization process today. The book examines ways in which fast food businesses have created a system of operation based on efficiency, calculability, predictability, and control; and how the same principles have been applied to other settings and contexts as diverse as motel chains,'big box' stores, churches, child care centers, college rankings, health care providers, the Internet, and political participation. The author also looks at attempts to resist and reverse the effects of McDonalization.'McDonalization' has become part of the lexicon of contemporary sociological theory, and the book has been widely adopted and read for over twenty years by hundreds of thousands of students in a wide variety of courses, including many courses created specifically to explore the phenomena of McDonaldization.
Preface -- Introduction To McDonaldization: -- McDonald's as an American and a global icon -- Long arm of McDonaldization -- Dimensions of McDonaldization: -- Efficiency -- Calculability -- Predictability -- Control -- Critique of McDonaldization: irrationality of rationality -- Illustrating the dimensions of McDonaldization: case of IKEA -- Advantages of McDonaldization -- What isn't McDonalized?: -- Are In-N-Out Burger and Pret A Manger antitheses of McDonaldization? -- In-N-Out Burger -- Pret A Manger -- Look ahead -- Past, Present, And Future Of McDonaldization: -- Bureaucratization: making life more rational: -- Weber's theory of rationality -- Irrationality and the'iron cage' -- Holocaust: mass-produced death -- Scientific management: finding the one best way -- Assembly line: turning workers into robots -- Levittown: putting up houses-'boom, boom, boom' -- Shopping centers: malling America -- McDonald's: creating the'fast-food factory' -- McDonaldization and contemporary social changes -- Forces driving McDonaldization: it pays, we value it, it fits: -- Higher profits and lower costs -- McDonaldization for its own sake -- McDonaldization and the changing society -- Other major social changes: McDonaldization in the era of the'posts': -- Postindustrialism and McDonaldization: complexification and simplification -- Fordism and post-Fordism: or is it McDonaldsim? -- Postmodernity: threat to McDonaldization? -- Future: are there any limits to the expansion of McDonaldization? -- Efficiency And Calculability: Consumers 1: -- Efficiency: drive-throughs and finger foods: -- Streamlining the process: -- Fast-food industry: speeding the way from secretion to excretion -- Home cooking (and related phenomena): I don't have time to cook -- Shopping: creating ever-more efficient selling machines -- Higher education: multitasking in McUniversity -- Health care: docs-in-a-box -- Entertainment: moving people (and trash) efficiently -- Online and smartphone dating: show your interest with just a'wink' -- Other settings: ten steps to spiritual maturity -- Simplifying the product -- Putting customers to work -- Calculability: Big Macs and little chips: -- Emphasizing quantity rather than quality of products: -- Fast-food industry: of'big bites' and'super big gulps' -- Higher education: grades and scores -- Predictability And Control: Consumers 2: -- Predictability: it never rains on those little houses on the hillside -- Predictable consumption settings: -- Motel chains: magic fingers but no Norman Bates -- Fast-food industry: thank God for those golden arches -- Other settings: E T can't find his home -- Predictable products and processes: -- Fast-food industry: even the pickles are standardized -- Entertainment: welcome to McMovieworld -- Minimizing danger and unpleasantness -- Control: human and nonhuman robots: -- Controlling consumers: -- Fast-food industry: get the hell out of there -- Other settings: it's like boot camp -- Ultimate examples of control: birth and death?: -- Controlling conception: even granny can conceive -- Controlling pregnancy: choosing the ideal baby -- Controlling childbirth: birth as pathology -- Controlling the process of dying: designer deaths -- Efficiency And Calculability: McJobs And Other McDonaldized Occupations 1: -- McJobs and the dimensions of McDonaldization -- Efficiency: it's a fetish: -- Fast-food industry: burger dressers in'factory stores' -- Academia: machine-grading and other efficiencies -- Medicine: assembly-line medicine -- Calculability: zeal for speed: -- Reducing production and service to numbers: -- Fast-food industry: hustle, and a precooked hamburger measures exactly 3-875 inches -- Workplace: penny the size of a cartwheel -- Academia: ratings and ranking -- Health care: patients as dollar signs -- Sports: Nadia Comaneci scored exactly 79-275 points -- Politics: there were no sound bites in the Lincoln-Douglas debate -- Predictability And Control: McJobs And Other McDonaldized Occupations 2: -- Predictability: scripting and controlling employees: -- Fast-food industry: howdy, pardner and'happy trails' -- Other settings: even the jokes are scripted and that Disney look -- Assembly line: cars more uniform than those produced by craftspeople -- Sports: there's even a McStables -- Control: even pilots aren't in control: -- Controlling employees: -- Workplace: do as I say, not as I do -- Fast-food industry: from human to mechanical robots -- Education: McChild care centers -- Health care: who's deciding our fate? -- Phoneheads and de-skilled pilots: it's like being in prison -- Controlling the process and the product: -- Food production: it cooks itself -- Food production: of sea farms and factory farms -- Irrationality Of Rationality: -- Inefficiency: long lines at the checkout -- High cost: better off at home -- False friendliness: Hi, George -- Disenchantment: where's the magic? -- Health and environmental hazards: day's calories in one fast-food meal -- Homogenization: it's no different in Paris -- Dehumanization: getting hosed at'troff'n' brew': -- Fast-food restaurants: like eating from a pig trough -- Family: kitchen as filling station -- Higher education: McLectures, McColleges, and MOOCs -- Health care: you're just a number -- Dehumanized death: dying amidst machines and strangers -- Irrationalities of McJobs: just hand the bag out -- Dealing With McDonaldization: -- Creating'reasonable' alternatives: sometimes you really do have to break the rules -- Fighting back collectively: saving hearts, minds, taste buds, and the Piazza di Spagna -- McLibel support group: McDonald's pyrrhic victory -- Slow food: creating a place for traditional, regional, and high-quality food -- Sprawl-busters: hit list of McDonaldized superstores -- Mobilizing to increase the minimum wage for fast-food workers: big profits, low pay -- Local protests: not wanting to say'bye-bye to the neighborhood -- Coping individually: skunk works, blindfolded children, and fantasy worlds -- Games, knitting, and nonrationalized niches -- Range of individual actions: if all else fails, save the children -- Freedom: if you can't cope, can you escape? -- Some concluding thoughts on dealing with McDonaldization -- Globalization And The Possibility Of The DeMcDonaldization Of Society?: -- Globalization and McDonaldization: -- Globalization of nothing: -- Nothing and something -- Glocalization and grobalization -- Grobalization of nothing -- DeMcDonaldization of society: -- Starbuckization -- What has Starbucks added to, or removed from, the McDonald's model? -- Should the concept of'Starbuckization' replace'McDonaldization'? -- Irrationality of rationality at Starbucks -- Internet and DeMcDonaldization eBayization -- eBayizing McDonaldization? -- Web 1-0 and 2-0 -- DeMcDonaldizing the Web? -- Notes -- Bibliography -- Index -- About the author.
Buku Bacaan Asas Fakulti
Includes bibliographical references : (pages 242-248) and index.
Text in English.
Keywords: Social structure -- United States; Management -- Social aspects -- United States; Fast food restaurants -- Social aspects -- United States; Rationalization (Psychology).; United States -- Social conditions -- 1980-